ANALISIS UJI BEDA TINGKAT EFISIENSI USAHATANI TEBU RAKYAT KREDIT DAN USAHATANI RAKYAT MANDIRI DI KOTA KEDIRI - Risqi Firdaus Setiawan; Hamidah Hendrarini (Jurnal Ilmiah Sosio Agribis, 2023)
This research was conducted to analyze the different levels of efficiency of the People's Credit Sugarcane (TRK) and Mandiri People's Sugarcane (TRM) farming businesses in Kediri City. The method used in determining farmer respondents used the Purposive Sampling method with the consideration of respondents, namely farmers with the Tebu Rakyat Kredit and Tebu Rakyat Mandiri (TRM) partnership pattern. 30 samples were obtained from 3 sub-districts. The data analysis method uses comparative analysis using the t-test, and efficiency between TRK and TRM uses the R/C ratio. The results of this research show that there is a difference in costs between TRK and TRM sugarcane farming, where TRK costs are higher than TRM costs, which are influenced by the amount of land area, the amount of sugarcane productivity, and the value of sugarcane yield. There is a difference in the amount of income between TRK and TRM sugar cane farmers, where TRK income is more significant than TRM costs. There is a difference in the efficiency of partnership sugar cane farming between TRK and TRM farmers, where TRK is more efficient than TRM. Keywords: T-test, Sugarcane, Efficiency, and Farming